Epidemiology and outcomes of acute promyelocytic leukaemia in the era of all-trans retinoic acid (ATRA) chemotherapy and arsenic trioxide plus ATRA: a retrospective analysis. (July 2022) - Gill, Harinder; Raghupathy, Radha; Ni, Michael; Xiao, Xiao; Flores, Francis; Lee, Carmen; Yim, Rita; Lee, Paul; Kumana, Cyrus; Kwong, Yok-Lam
Abstract: Background: Acute promyelocytic leukaemia (APL) results from the reciprocal chromosomal translocation t(15;17)(q24;21) ( PML–RARA gene fusion). We have formulated an oral, economical, and outpatient-based preparation of arsenic trioxide and shown that it is efficacious for newly diagnosed and relapsed APL. In this study, we aimed to define the epidemiological landscape of APL in Hong Kong and to assess the effect of oral arsenic trioxide therapy on patient outcomes. Methods: This retrospective analysis of patients diagnosed with APL in Hong Kong between Jan 1, 1991, and March 31, 2021 (data censored on Nov 30, 2021) had incidence of APL, early death (within 30 days of hospitalisation), and overall survival as primary outcomes, and incidence of other primary cancers as a secondary outcome. Oral all-trans retinoic acid (ATRA) plus chemotherapy or oral arsenic trioxide were used. ATRA plus chemotherapy comprised induction with ATRA (45 mg/m 2 per day, divided in two doses, for 42 days) and daunorubicin (50 mg/m 2 per day intravenously for 3 days); consolidation with two cycles of daunorubicin (for 2 days) and cytarabine (100 mg/m 2 per day intravenously for 5 days); and 24 months of maintenance therapy with ATRA (for 15 days every 3 months), 6-mercaptopurine (90 mg/m 2 per day), and methotrexate (15 mg/m 2 per week). The arsenic trioxide approach comprised two dosing schedules: for patients diagnosed between Jan 1, 2013, and Dec 31, 2017, arsenic trioxide was included in induction and maintenance only; induction was with arsenic trioxide (0·15 mg/day for 42 days), ATRA, oral ascorbic acid (1000 mg/day for 42 days), and daunorubicin; consolidation was with two cycles of daunorubicin and cytarabine; and 24 months of maintenance with arsenic trioxide, ATRA, and ascorbic acid (all for 14 days every 2 months). For patients diagnosed between Jan 1, 2018, and March 31, 2022, arsenic trioxide was included in induction, consolidation, and maintenance, substantially reducing exposure to chemotherapy; induction was with arsenic trioxide (0·15 mg/kg per day for 42 days), ATRA and ascorbic acid (for 42 days), and daunorubicin (given only to patients presenting with a leucocyte count of 10 × 10 9 cells/L); consolidation was with two cycles of arsenic trioxide, ATRA, and ascorbic acid (all for 14 days every 28 days); and 24 months of maintenance therapy with arsenic trioxide, ATRA, and ascorbic acid. Multivariate cox regression analysis was used to find prognostic indicators for overall survival. This ongoing study was approved by the University of Hong Kong's Institutional Review Board and is registered with ClinicalTrials.gov, NCT04251754 . Findings: 751 patients (387 [51%] women and 364 [49%] men) were identified (median age 44 years [IQR 31–57]), for an annual incidence of 0·32 per 100 000 people. 469 (62%) patients received ATRA plus chemotherapy and 282 (38%) patients received oral arsenic trioxide. After a median follow-up of 75 months (IQR 14–161), 271 (36%) patients had died, with early death constituting 144 (53%) cases, all occurring in patients in the ATRA plus chemotherapy cohort. 5-year overall survival in the full cohort was 68% and 10-year overall survival was 63%. On multivariate analysis, being male (p=0·019), older than 50 years (p<0·0001), having a leucocyte count of >10 × 10 9 cells/L at presentation (p<0·0001), and having ATRA plus chemotherapy regimens (p<0·0001) were all associated with worse overall survival. In the oral arsenic trioxide cohort, 5-year overall survival was 92% and 10-year overall survival was 85%. In the ATRA plus chemotherapy cohort, 5-year overall survival was 55% and 10-year overall survival was 51%. Second cancers developed in 21 patients (eight never exposed to oral arsenic trioxide; 13 with previous exposure to oral arsenic trioxide during induction, maintenance, or relapse). The incidence of second cancers in patients exposed to oral arsenic trioxide did not differ from that in patients never exposed to oral arsenic trioxide (incidence rate ratio 2·14 [95% CI 0·89–5·17], p=0·099). Interpretation: Oral arsenic trioxide plus ATRA was associated with fewer early deaths and better long-term survival than ATRA plus chemotherapy, with shorter hospital stays and outpatient treatment as distinct health-care advantages. Funding: Health and Medical Research Fund of the Hong Kong Special Administrative Region, China (code 08191946).